Implementation of green public procurement in public transport: criteria analysis and proposals evaluation - Janaine F. G. Timm; Michelle Zanettini Leichter; Julia Martini Dalmoro; Ana Passuello (Clean Technologies and Environmental Policy, 2025)

Corrigendum to “BCL-3 loss sensitises colorectal cancer cells to DNA damage by targeting homologous recombination” [DNA Repair 115 (2022) 103331] - Christopher Parker; Adam C. Chambers; Dustin J. Flanagan; Jasmine Wing Yu Ho; Tracey J. Collard; Greg Ngo; Duncan M. Baird; Penny Timms; Rhys G. Morgan; Owen J. Sansom; Ann C. Williams (DNA Repair, 2025)

Cost–benefit analysis of ecosystem modeling to support fisheries management - Matthew H. Holden; Eva E. Plagányi; Elizabeth A. Fulton; Alexander B. Campbell; Rachel Janes; Robyn A. Lovett; Montana Wickens; Matthew P. Adams; Larissa Lubiana Botelho; Catherine M. Dichmont; Philip Erm; Kate J. Helmstedt; et al. (Journal of Fish Biology, 2024)
Mathematical and statistical models underlie many of the world's most important fisheries management decisions. Since the 19th century, difficulty calibrating and fitting such models has been used to justify the selection of simple, stationary, single‐species models to aid tactical fisheries management decisions. Whereas these justifications are reasonable, it is imperative that we quantify the value of different levels of model complexity for supporting fisheries management, especially given a changing climate, where old methodologies may no longer perform as well as in the past. Here we argue that cost‐benefit analysis is an ideal lens to assess the value of model complexity in fisheries management. While some studies have reported the benefits of model complexity in fisheries, modeling costs are rarely considered. In the absence of cost data in the literature, we report, as a starting point, relative costs of single‐species stock assessment and marine ecosystem models from two Australian organizations. We found that costs varied by two orders of magnitude, and that ecosystem model costs increased with model complexity. Using these costs, we walk through a hypothetical example of cost‐benefit analysis. The demonstration is intended to catalyze the reporting of modeling costs and benefits.

Importance of methodological pluralism in deriving counterfactuals for evidence‐based conservation - Petra Holden; Molly Anderson; Frank Eckardt; Gina Ziervogel; Samuel L. Jack; Mark G. New; Julian Smit; Martine Visser; M. Timm Hoffman (Conservation Biology, 2024)
Most protected area impact research that uses counterfactuals draws heavily on quantitative methods, data, and knowledge types, making it valuable in producing generalizations but limited in temporal scope, historical detail, and habitat diversity and coverage of ecosystem services. We devised a methodological pluralistic approach, which supports social science qualitative methods, narratives, mixed methods, and interdisciplinarity, to fully unlock the potential of counterfactuals in ensuring a place‐based and detailed understanding of the socioecological context and impacts of protected areas. We applied this approach to derive possible counterfactual conditions for the impact of a montane protected area on 40 years of vegetation change in the Cape Floristic Region—a global biodiversity hotspot and UNESCO World Heritage Site in South Africa. We incorporated diverse methods, knowledge, and information sources, drawing on before–after protected area comparisons for inside and outside the protected area. A significant increase in shrubland vegetation (17–30%) was observed and attributed primarily to a decline in frequent burning for grazing. This also occurred outside the protected area and was driven by socioeconomic drivers and not by concerns over biodiversity conservation or land degradation. Had the protected area not been established the area would have seen intensification of cultivation and increased road networks, buildings, and water storage in dams. Our approach increased historical temporal coverage of socioecological change and contextualized assumptions around causality. Protected area impact evaluation should reengage in place‐based research that fully incorporates pluralism in methodologies for constructing counterfactuals in a way that builds regional and global understanding from the local level upward. We devised 10 key principles for deriving counterfactuals grounded in methodological pluralism, covering aspects of collaboration, cocreation, inter‐ and transdisciplinarity, diverse values and lived experiences, multiple knowledge types, multiple possible causal mechanisms, social science qualitative methods, perceptions, perspectives, and narratives.

Complexation of Zr and Hf in fluoride-rich hydrothermal aqueous fluids and its significance for high field strength element fractionation - Anselm Loges; Marco Manni; Marion Louvel; Max Wilke; Sandro Jahn; Edmund Welter; Manuela Borchert; Shilei Qiao; Stephan Klemme; Bettina G. Keller; Timm John (Geochimica et Cosmochimica Acta, 2024)

Effects of systematic predictor selection for statistical downscaling of rainfall in Hawai'i - Kristen Sanfilippo; Oliver Elison Timm; Abby G. Frazier; Thomas W. Giambelluca (International Journal of Climatology, 2024)
While there has been rapid advancement in the development and application of statistical downscaling methods for climate projection, determining the best predictive large‐scale climate information for the targeted local climate variable remains a challenge. The choice of predictor variables is one of the most influential steps of model development and has the potential to lead to varying results, contributing to the total uncertainty of future projections. Despite being a well‐known problem, predictor selection often does not receive adequate attention and the development of a straightforward and feasible prescreening process is needed to provide guidance to simple (e.g., linear regression) and complex (e.g., machine learning) modeling tools alike. In this project, Akaike information criterion (AIC) and leave one out cross validation are used to evaluate sets of predictor variables common in statistical downscaling models of precipitation (e.g., temperature, geopotential height, moisture transport). Because thousands of predictor sets were found to be competitive in their statistical skill in projecting rainfall, results suggest that an ensemble of predictor sets should be used to account for the resulting variance associated with predictor selection. This ensemble approach is applied to make improvements to the most recent statistical downscaling model developed for rainfall projection in Hawai'i. An ensemble validation study is performed by projecting future wet season rainfall in Hawai'i for scenario RCP4.5 using 17 CMIP5 GCMs with ensembles of highly ranked and poorly ranked predictor sets. Results show significantly less variance and improved agreement in the projected sign of precipitation change for the highly ranked predictor set ensemble. In conclusion, it is recommended that statistical downscaling models are run in an ensemble‐mode with multiple combinations of predictors instead of using a single model, allowing for additional quantification of model uncertainty and a “safety net” for when the true physically best‐suited predictor set is unknown.

Reconstruction of short-term storm surge-driven increases in shallow coastal lake salinity using ostracod shell chemistry - Lucy R. Roberts; Jonathan A. Holmes; David J. Horne; Melanie J. Leng; Carl D. Sayer; Rhys G. O. Timms; Katy Flowers; Simon P. M. Blockley; Andrea Kelly (Natural Hazards, 2022)

Middle Pleistocene environments, landscapes and tephrostratigraphy of the Armenian Highlands: evidence from Bird Farm 1, Hrazdan Valley - Jenni E. Sherriff; Keith N. Wilkinson; Poppy Harding; Hayley Hawkins; Rhys G. O. Timms; Daniel S. Adler; Emily J. Beverly; Simon P. E. Blockley; Boris Gasparyan; Christina J. Manning; Darren Mark; Samvel Nahapetyan; et al. (Journal of Quaternary Science, 2022)
The significance of the southern Caucasus in understanding Pleistocene hominin expansions is well established. However, the palaeoenvironments in which Palaeolithic occupation of the region took place are presently poorly defined. The Hrazdan river valley, Armenian Highlands, contains a rich Palaeolithic record alongside Middle Pleistocene volcanic, fluvial and lacustrine strata, and thus offer exciting potential for palaeoenvironmental reconstruction. We present the first results of sedimentological, geochemical, tephrostratigraphical and biological (diatoms) study of the sequence of Bird Farm 1, located in the central part of the valley. These data show six phases of landscape development during the interval 440–200 ka. The sequence represents the first quantitative Pleistocene diatom record from the Armenian Highlands and the southern Caucasus, and indicates the persistence of a deep, stratified lacustrine system, with evidence for changing lake productivity that is tentatively linked to climate. Furthermore, major element chemical characterization of visible and crypto‐tephra horizons in the sequence enables the first stages of the development of a regional tephrostratigraphy. Together, the evidence from Bird Farm 1 demonstrates the importance of lacustrine archives in the region for palaeoenvironmental reconstruction and highlights the potential for linkages between archives on both a local and regional scale.

Acute effects of the imidacloprid metabolite desnitro-imidacloprid on human nACh receptors relevant for neuronal signaling - Dominik Loser; Karin Grillberger; Maria G. Hinojosa; Jonathan Blum; Yves Haufe; Timm Danker; Ylva Johansson; Clemens Möller; Annette Nicke; Susanne H. Bennekou; Iain Gardner; Caroline Bauch; et al. (Archives of Toxicology, 2021)
Several neonicotinoids have recently been shown to activate the nicotinic acetylcholine receptor (nAChR) on human neurons. Moreover, imidacloprid (IMI) and other members of this pesticide family form a set of diverse metabolites within crops. Among these, desnitro-imidacloprid (DN-IMI) is of special toxicological interest, as there is evidence (i) for human dietary exposure to this metabolite, (ii) and that DN-IMI is a strong trigger of mammalian nicotinic responses. We set out here to quantify responses of human nAChRs to DN-IMI and an alternative metabolite, IMI-olefin. To evaluate toxicological hazards, these data were then compared to those of IMI and nicotine. Ca 2+ -imaging experiments on human neurons showed that DN-IMI exhibits an agonistic effect on nAChRs at sub-micromolar concentrations (equipotent with nicotine) while IMI-olefin activated the receptors less potently (in a similar range as IMI). Direct experimental data on the interaction with defined receptor subtypes were obtained by heterologous expression of various human nAChR subtypes in Xenopus laevis oocytes and measurement of the transmembrane currents evoked by exposure to putative ligands. DN-IMI acted on the physiologically important human nAChR subtypes α7, α3β4, and α4β2 (high-sensitivity variant) with similar potency as nicotine. IMI and IMI-olefin were confirmed as nAChR agonists, although with 2–3 orders of magnitude lower potency. Molecular docking studies, using receptor models for the α7 and α4β2 nAChR subtypes supported an activity of DN-IMI similar to that of nicotine. In summary, these data suggest that DN-IMI functionally affects human neurons similar to the well-established neurotoxicant nicotine by triggering α7 and several non-α7 nAChRs.

Riparian populations of minnesota reed canarygrass (Phalaris arundinacea) are most likely native, based on SNPs (DArTseqLD) - Andrzej K. Noyszewski; Neil O. Anderson; Alan G. Smith; Andrzej Kilian; Diana Dalbotten; Emi Ito; Anne Timm; Holly Pellerin; Barbora Kubátová; Tereza Kávová; Vojtěch Januš; Vladislav Čurn; et al. (Wetlands Ecology and Management, 2021)
The native vs. exotic status of reed canarygrass (RCG), a major invasive species of Minnesota wetlands, is unknown. The aim of this study was to investigate this native vs. exotic status to enhance its management. Genetic comparison of wild RCG populations from six Minnesota and six Czech Republic rivers was performed. A total of 2521 polymorphic SNP markers (single nucleotide polymorphisms) were used to evaluate 478 RCG samples across all collections. In the PCoA, all (n = 256) tested extant wild, riparian RCG genotypes from six Minnesota Rivers and six Czech Republic Rivers were genetically distinct, although some SNPs were common in both populations since they are the same species. DAPC analysis also resulted in the formation of two primary clusters separating the Minnesota Rivers and Czech Republic Rivers riparian samples, with little overlap; STRUCTURE analysis also supported this clustering with k = 4 groups as it separated the Czech Republic Rivers populations into three groups, along with Minnesota Rivers. The uniformity of PCoA, DAPC, STRUCTURE, and Evanno results indicates the distinct separation of Minnesota Rivers and Czech Republic Rivers populations. Portions of the genome (specific SNPs) are preserved or in common across continents, as indicated by STRUCTURE similarities. Nonetheless, overall significant SNP differences between the continents indicate that the Minnesota riparian populations are distinct enough from the European (Czech) collections to be delineated as native N. American RCG. PCoA of all the Minnesota RCG collections clustered Minnesota Rivers, Herbarium, Extant Herbarium, Research Field and Native Field collections together. STRUCTURE analysis (k = 2; Evanno) divided these Minnesota collections from the Commercial Field and Cultivars collections. There are two genetically distinct groups of RCG in Minnesota and since the Minnesota Rivers, the Research Field, the Native Field and pre-1930 herbaria collections clustered together, they are most likely native N. American types. Analysis of molecular variance (AMOVA) indicated that the genetic variation was more significant within, rather than among, the RCG populations. Native, historic herbaria types cluster together with all wild RCG river populations in Minnesota, all of which were distinct from those in Central Europe, suggesting native RCG type persistence in N. America. Also, cultivated forage types of RCG are distinct from wild RCG Minnesota river populations. The SNP genetic data shows that riparian Minnesota RCG populations are native. These data will facilitate future management strategies to control RCG as a native, but invasive, species.

Functional alterations by a subgroup of neonicotinoid pesticides in human dopaminergic neurons - Dominik Loser; Maria G. Hinojosa; Jonathan Blum; Jasmin Schaefer; Markus Brüll; Ylva Johansson; Ilinca Suciu; Karin Grillberger; Timm Danker; Clemens Möller; Iain Gardner; Gerhard F. Ecker; et al. (Archives of Toxicology, 2021)
Neonicotinoid pesticides, originally developed to target the insect nervous system, have been reported to interact with human receptors and to activate rodent neurons. Therefore, we evaluated in how far these compounds may trigger signaling in human neurons, and thus, affect the human adult or developing nervous system. We used SH-SY5Y neuroblastoma cells as established model of nicotinic acetylcholine receptor (nAChR) signaling. In parallel, we profiled dopaminergic neurons, generated from LUHMES neuronal precursor cells, as novel system to study nAChR activation in human post-mitotic neurons. Changes of the free intracellular Ca 2+ concentration ([Ca 2+ ] i ) were used as readout, and key findings were confirmed by patch clamp recordings. Nicotine triggered typical neuronal signaling responses that were blocked by antagonists, such as tubocurarine and mecamylamine. Pharmacological approaches suggested a functional expression of α7 and non-α7 nAChRs on LUHMES cells. In this novel test system, the neonicotinoids acetamiprid, imidacloprid, clothianidin and thiacloprid, but not thiamethoxam and dinotefuran, triggered [Ca 2+ ] i signaling at 10–100 µM. Strong synergy of the active neonicotinoids (at low micromolar concentrations) with the α7 nAChR-positive allosteric modulator PNU-120596 was observed in LUHMES and SH-SY5Y cells, and specific antagonists fully inhibited such signaling. To provide a third line of evidence for neonicotinoid signaling via nAChR, we studied cross-desensitization: pretreatment of LUHMES and SH-SY5Y cells with active neonicotinoids (at 1–10 µM) blunted the signaling response of nicotine. The pesticides (at 3–30 µM) also blunted the response to the non-α7 agonist ABT 594 in LUHMES cells. These data show that human neuronal cells are functionally affected by low micromolar concentrations of several neonicotinoids. An effect of such signals on nervous system development is a toxicological concern.

A multi‐proxy record of abrupt cooling events during the Windermere Interstadial at Crudale Meadow, Orkney, UK - Christopher P. Francis; Stefan Engels; Ian P. Matthews; Adrian P. Palmer; Rhys G. O. Timms; Anne‐Lise Jourdan; Ian Candy (Journal of Quaternary Science, 2021)
Three clearly defined abrupt cooling events (ACEs) can be observed within Greenland Interstadial (GI)‐1 in the Greenland ice‐core records. However, the spatial variation in amplitude and timing of these ACEs is poorly understood due to the paucity of well‐dated records with quantified temperature reconstructions. This study presents high‐resolution chironomid‐inferred July air temperature (T Jul ) and oxygen isotope (δ 18 O) records from Crudale Meadow (Orkney Isles, UK). Three centennial‐scale ACEs punctuate the Windermere Interstadial at Crudale Meadow. The largest ACE shows an amplitude of 5.4 °C and a 1% isotopic decline and is centred on ~14.0 ka bp , consistent with the timing of the GI‐1d event in the Greenland stratigraphy. The two other observed ACEs are of smaller magnitude and are centred on ~13.6 ka bp and ~13.2 ka bp , with these smaller magnitude events tentatively correlated with the GI‐1cii and GI‐1b events, respectively, but lack sufficient chronological constraint to fully assess their timing. When comparing the Crudale Meadow record with other locations in the British Isles a strong relationship can be observed between the magnitude of T Jul cooling and latitude, with a reduced signal in more southerly locations, indicating that oceanic forcing may be a key driver of the ACEs.

Evidence for centennial‐scale Lateglacial and early Holocene climatic complexity from Quoyloo Meadow, Orkney, Scotland - Rhys G. O. Timms; Ashley M. Abrook; Ian P. Matthews; Christopher P. Francis; Agnieszka Mroczkowska; Ian Candy; Stephen J. Brooks; Alice M. Milner; Adrian P. Palmer (Journal of Quaternary Science, 2021)
The influence of the North Atlantic on the margins of Europe means the region is particularly sensitive to changes in the ocean–atmospheric system. During the Last Glacial–Interglacial Transition (16–8 cal ka bp ) this system was repeatedly disrupted, leading to a series of abrupt and short‐lived shifts in climate. Despite much research, the number and magnitude of these ‘centennial‐scale’ events is not well understood. To address this, we expand upon investigations at Quoyloo Meadow, Orkney, Scotland, one of the best chronologically constrained palaeoclimate records in northern Britain. By coupling stable isotope and chironomid fossil analyses with existing data, this study identifies multiple phases of centennial‐scale disturbance at: c . 14.0, 11.1, 10.8, 10.5, 10.45 and 10.3 cal ka bp , with the events at 14.0 and 10.3 exhibiting a particularly pronounced cold‐climate signature. During the Holocene, the strongest response to climate forcing was at c . 10.3–10.0 cal ka bp , expressed as a two‐stage drop in mean July temperatures, a shift in pollen spectra indicative of ‘less‐stable’ climatic regimes, and a depletion in δ 18 O values. We interpret this as the first reliably dated incidence of the ‘10.3‐ka event’ in the British Isles and consider the wider impact of this climatic reversal in other Holocene records.

Investigation of Visual System Involvement in Spinocerebellar Ataxia Type 14 - Thomas Ihl; Ella M. Kadas; Timm Oberwahrenbrock; Matthias Endres; Thomas Klockgether; Jan Schroeter; Alexander U. Brandt; Friedemann Paul; Martina Minnerop; Sarah Doss; Tanja Schmitz-Hübsch; Hanna G. Zimmermann (The Cerebellum, 2020)
Spinocerebellar ataxia type 14 (SCA-PRKCG, formerly SCA14) is a rare, slowly progressive disorder caused by conventional mutations in protein kinase Cγ (PKCγ). The disease usually manifests with ataxia, but previous reports suggested PRKCG variants in retinal pathology. To systematically investigate for the first time visual function and retinal morphology in patients with SCA-PRKCG. Seventeen patients with PRKCG variants and 17 healthy controls were prospectively recruited, of which 12 genetically confirmed SCA-PRKCG patients and 14 matched controls were analyzed. We enquired a structured history for visual symptoms. Vision-related quality of life was obtained with the National Eye Institute Visual Function Questionnaire (NEI-VFQ) including the Neuro-Ophthalmic Supplement (NOS). Participants underwent testing of visual acuity, contrast sensitivity, visual fields, and retinal morphology with optical coherence tomography (OCT). Measurements of the SCA-PRKCG group were analyzed for their association with clinical parameters (ataxia rating and disease duration). SCA-PRKCG patients rate their vision-related quality of life in NEI-VFQ significantly worse than controls. Furthermore, binocular visual acuity and contrast sensitivity were worse in SCA-PRKCG patients compared with controls. Despite this, none of the OCT measurements differed between groups. NEI-VFQ and NOS composite scores were related to ataxia severity. Additionally, we describe one patient with a genetic variant of uncertain significance in the catalytic domain of PKCγ who, unlike all confirmed SCA-PRKCG, presented with a clinically silent epitheliopathy. SCA-PRKCG patients had reduced binocular vision and vision-related quality of life. Since no structural retinal damage was found, the pathomechanism of these findings remains unclear.

The influence of ENSO, PDO and PNA on secular rainfall variations in Hawai‘i - Abby G. Frazier; Oliver Elison Timm; Thomas W. Giambelluca; Henry F. Diaz (Climate Dynamics, 2018)

Multi-criteria correlation of tephra deposits to source centres applied in the Auckland Volcanic Field, New Zealand - Jenni L. Hopkins; Colin J. N. Wilson; Marc-Alban Millet; Graham S. Leonard; Christian Timm; Lucy E. McGee; Ian E. M. Smith; Euan G. C. Smith (Bulletin of Volcanology, 2017)

Late Cenozoic paleovalley fill sequence from the Southern Liverpool Plains, New South Wales—implications for groundwater resource evaluation - R. I. Acworth; W. A. Timms; B. F. J. Kelly; D. E. Mcgeeney; T. J. Ralph; Z. T. Larkin; G. C. Rau (Australian Journal of Earth Sciences, 2015)

3D structural and stratigraphic model of the Perth Basin, Western Australia: Implications for sub-basin evolution - H. K. H. Olierook; N. E. Timms; J. F. Wellmann; S. Corbel; P. G. Wilkes (Australian Journal of Earth Sciences, 2015)

Paleodrainage and fault development in the southern Perth Basin, Western Australia during and after the breakup of Gondwana from 3D modelling of the Bunbury Basalt - H. K. H. Olierook; N. E. Timms; R. E. Merle; F. Jourdan; P. G. Wilkes (Australian Journal of Earth Sciences, 2015)

Temporal processes of soil water status in a sugarcane field under residue management - G. O. Awe; J. M. Reichert; L. C. Timm; O. O. Wendroth (Plant and Soil, 2015)

Improved sea level record over the satellite altimetry era (1993–2010) from the Climate Change Initiative project - M. Ablain; A. Cazenave; G. Larnicol; M. Balmaseda; P. Cipollini; Y. Faugère; M. J. Fernandes; O. Henry; J. A. Johannessen; P. Knudsen; O. Andersen; J. Legeais; et al. (Ocean Science, 2015)
Sea level is one of the 50 Essential Climate Variables (ECVs) listed by the Global Climate Observing System (GCOS) in climate change monitoring. In the past two decades, sea level has been routinely measured from space using satellite altimetry techniques. In order to address a number of important scientific questions such as "Is sea level rise accelerating?", "Can we close the sea level budget?", "What are the causes of the regional and interannual variability?", "Can we already detect the anthropogenic forcing signature and separate it from the internal/natural climate variability?", and "What are the coastal impacts of sea level rise?", the accuracy of altimetry-based sea level records at global and regional scales needs to be significantly improved. For example, the global mean and regional sea level trend uncertainty should become better than 0.3 and 0.5 mm year−1, respectively (currently 0.6 and 1–2 mm year−1). Similarly, interannual global mean sea level variations (currently uncertain to 2–3 mm) need to be monitored with better accuracy. In this paper, we present various data improvements achieved within the European Space Agency (ESA) Climate Change Initiative (ESA CCI) project on "Sea Level" during its first phase (2010–2013), using multi-mission satellite altimetry data over the 1993–2010 time span. In a first step, using a new processing system with dedicated algorithms and adapted data processing strategies, an improved set of sea level products has been produced. The main improvements include: reduction of orbit errors and wet/dry atmospheric correction errors, reduction of instrumental drifts and bias, intercalibration biases, intercalibration between missions and combination of the different sea level data sets, and an improvement of the reference mean sea surface. We also present preliminary independent validations of the SL_cci products, based on tide gauges comparison and a sea level budget closure approach, as well as comparisons with ocean reanalyses and climate model outputs.

A novel link between Campylobacter jejuni bacteriophage defence, virulence and Guillain–Barré syndrome - R. Louwen; D. Horst-Kreft; A. G. Boer; L. Graaf; G. Knegt; M. Hamersma; A. P. Heikema; A. R. Timms; B. C. Jacobs; J. A. Wagenaar; H. P. Endtz; J. Oost; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Biventricular Assist Devices: A Technical Review - Shaun D. Gregory; Daniel Timms; Nicholas Gaddum; David G. Mason; John F. Fraser (Annals of Biomedical Engineering, 2011)

Feasibility of Using a Computer Modeling Approach to Study SUI Induced by Landing a Jump - Yingchun Zhang; Seoggwan Kim; Arthur G. Erdman; Kenneth P. Roberts; Gerald W. Timm (Annals of Biomedical Engineering, 2009)

Western Indian Ocean marine and terrestrial records of climate variability: a review and new concepts on land–ocean interactions since AD 1660 - J. Zinke; M. Pfeiffer; O. Timm; W.-Ch. Dullo; G. J. A. Brummer (International Journal of Earth Sciences, 2009)

Investigating the mechanisms of photosynthetic proteins using continuum electrostatics - G. Matthias Ullmann; Edda Kloppmann; Timm Essigke; Eva-Maria Krammer; Astrid R. Klingen; Torsten Becker; Elisa Bombarda (Photosynthesis Research, 2008)

Differential Response of Aquatic Oligochaete Species to Increased Nutrient Availability – a Comparative Study between Estonian and Dutch Raised Bogs - G. A. van Duinen; T. Timm; A. J. P. Smolders; A. M. T. Brock; W. C. E. P. Verberk; H. Esselink (Hydrobiologia, 2006)

Effects of Changing Forest and Impervious Land Covers on Discharge Characteristics of Watersheds - Robert C. Wissmar; Raymond K. Timm; Miles G. Logsdon (Environmental Management, 2004)

Genetic transformation of Dichanthium annulatum (Forssk)?an apomictic tropical forage grass - S. J. Dalton; A. J. E. Bettany; V. Bhat; M. G. Gupta; K. Bailey; E. Timms; P. Morris (Plant Cell Reports, 2003)

Flow cytometric analysis of lymphocyte subpopulations in bronchoalveolar lavage fluid after repeated ozone exposure - O. Holz; M. Böttcher; P. Timm; S. Koschyk; G. Abel; G. Gercken; H. Magnussen; R. A. Jörres (International Archives of Occupational and Environmental Health, 2001)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Formation of poly(3-hydroxyalkanoates) by phototrophic and chemolithotrophic bacteria - Matthias Liebergesell; Eilert Hustede; Arnulf Timm; Alexander Steinbüchel; R. Clinton Fuller; Robert W. Lenz; Hans G. Schlegel (Archives of Microbiology, 1991)

Life members announced - Herman Timm; R. G. Rowberry; Gene Shaver; Robert W. Goth; William G. Hoyman (American Journal of Potato Research, 1980)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

s of papers presented at the Fifty-Second Annual Meeting of The Potato Association of America - J. A. Crozier; P. J. Ito; Puente De La Fermin; S. J. Peloquin; P. Severino; E. C. Doll; D. R. Christenson; A. R. Wolcott; Hawkins Arthur; F. D. Howard; Herman Timm; W. J. Flocker; et al. (American Journal of Potato Research, 1968)

Erratum - Herman Timm; M. Yamaguchi; M. D. Clegg; J. C. Bishop; Guy W. Bishop; G. C. Upreti; B. B. Nagaich; E. F. Maas; J. P. Sweeney; V. J. Chapman; P. A. Hepner; R. M. Reeve (American Journal of Potato Research, 1968)

The influence of chlorides on yield and specific gravity of potatoes - Herman Timm; F. G. Merkle (American Journal of Potato Research, 1963)